If only I had time: Teachers’ perceptions of teaching high-ability science students - Horsley, Jenny; Moeed, Azra (New Zealand Science Review, 2017)
​With many countries relying on science and technology for their economic prosperity, science educators are tasked with nurturing curiosity and encouraging high-ability science students to become creative and innovative scientists of the future. This exploratory case study employed semi-structured interviews to investigate how four award-winning science teachers identified and addressed the learning needs of their high-ability science students. The research was underpinned by a constructivist theory of learning. Findings suggest that these teachers were not aware of mandated policies for Gifted and Talented students. They used English and mathematics standardised tests for identifying high-ability science students, supplemented with their own approaches to identification. Although literature identifies the importance of student-led science inquiry, we found no evidence of the teachers engaging their students in authentic scientific inquiry to enable them to investigate their own questions. These findings are discussed in the light of extant literature. Keywords: high-ability science students; gifted and talented in science; identification of high-ability science students